The Mediating Role of Marital Burnout in the Relationship Between Attachment Needs and Couples’ Tendency Toward Divorce - Khorshidi, Elaheh; Samani, Siamak (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the mediating role of marital burnout in the relationship between attachment needs and couples’ tendency toward divorce in the city of Shiraz. This applied study was conducted using a correlational design based on structural equation modeling. The statistical population included all married couples in Shiraz in 2025, from whom 200 participants were selected through convenience sampling. The research instruments included the Divorce Tendency Questionnaire developed by Rosebelt, Johnson, and Morrow, the Marital Burnout Questionnaire by Pines, and the Attachment Needs Questionnaire developed by Samani et al. Data were analyzed using SPSS version 21 and AMOS software. In the descriptive section, mean and standard deviation were used, while Pearson correlation coefficient and structural equation modeling were employed in the inferential section. The results indicated that attachment needs had a significant negative relationship with marital burnout (r = -0.524, p < 0.001) and tendency toward divorce (r = -0.474, p < 0.001). In addition, marital burnout showed a significant positive relationship with tendency toward divorce (r = 0.417, p < 0.001). The findings of the structural equation model demonstrated that the path from attachment needs to marital burnout (β = -0.748), the path from attachment needs to tendency toward divorce (β = -0.415), and the path from marital burnout to tendency toward divorce (β = 0.162) were all significant (p < 0.001). Furthermore, the indirect effect of attachment needs on tendency toward divorce through marital burnout was equal to 0.132, confirming the significant mediating role of marital burnout. The findings of the study indicated that unmet attachment needs can increase couples’ tendency toward divorce through heightened marital burnout. Therefore, paying attention to couples’ emotional and affective needs and designing interventions based on attachment-oriented and emotion-focused approaches may play an effective role in reducing marital burnout and preventing divorce.